2013
DOI: 10.1016/j.jmmm.2013.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Necrosis of HepG2 cancer cells induced by the vibration of magnetic particles

Abstract: International audienceExperiments of magnetolysis, i.e., destruction of cells induced with magnetic particles (MPs) submitted to the application of a magnetic field, were conducted on HepG2 cancer cells. We herein demonstrate the usefulness of combining anisotropic MPs with an alternative magnetic field in magnetolysis. Thus, the application of an alternative magnetic field of low frequency (a few Hertz) in the presence of anisotropic, submicronic particles allowed the destruction of cancer cells "in vitro". W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…Magnetic micro-and nanoparticles and their liquid suspensions or gels are gaining a growing interest in environmental and biomedical applications, such as water purification from organic and inorganic molecules 1,2 , magnetic resonance imaging 3,4 , cell separation 5 , protein purification 6,7 , magnetic hyperthermia 8,9 , controlled drug delivery and release 10,11 , magnetomechanical lysis of tumor cells 12,13 , high sensitivity immunoassays 14 and tissue engineering 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic micro-and nanoparticles and their liquid suspensions or gels are gaining a growing interest in environmental and biomedical applications, such as water purification from organic and inorganic molecules 1,2 , magnetic resonance imaging 3,4 , cell separation 5 , protein purification 6,7 , magnetic hyperthermia 8,9 , controlled drug delivery and release 10,11 , magnetomechanical lysis of tumor cells 12,13 , high sensitivity immunoassays 14 and tissue engineering 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In particular, magnetic nanoparticles are very promising for the treatment of serious diseases such as cancer. [7][8][9] For this purpose, anisotropic magnetic particles were used to exert forces or torques on cancer cells. More recently, some novel approaches were developed to destroy cancer cells based on low frequency mechanical effects on the cancer cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…For example, magnetic nanoparticlemediated intracellular hyperthermia has been showing promising results in destroying tumours thanks to a local heating of the cells produced by alternating magnetic field oscillating at hundreds of kHz. Some of these approaches induce necrosis of the cells by destroying the cell integrity by mechanical disruption of their membrane (magnetoporation) or disruption of the whole cell (magnetolysis) 7,9 or even of the tumor itself. [7][8][9] For this purpose, anisotropic magnetic particles were used to exert forces or torques on cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…It demonstrated that neither the static magnetic field nor the rotating one results in any cell damage, as quantified by measuring the cells' metabolic activity (relative to untreated control cells) the day after the magnetic stimulations. The nanorods/cell membrane interactions thus do not induce any significant alteration of cells viability and proliferation capacity, even in the rotating setting, contrary to some other studies reporting membrane physical rupture triggered by rotating magnetic nanoparticles, generally targeted to a specific receptor . Here, it shows that cells can also adapt to a rotating stress and avoid massive harm.…”
mentioning
confidence: 48%
“…In magnetic manipulation of cell membranes, an external rotating magnetic field is used to act at a distance, with precisely controlled intensity, direction, and localization of the applied magnetic torque. Magnetically driven rotating or oscillating magnetic nanoparticles could thus be used to probe cells' mechanical properties, to deliver drugs, or to kill cells by physical membrane rupture . In this last application, anisotropic nanoparticles in disk‐ or rod‐like shapes, stimulated with low‐frequency magnetic fields, could compromise the cell membrane and thereby trigger apoptotic or necrotic programed cell death.…”
mentioning
confidence: 99%